IMPLEMENTASI APLIKASI KEWIRAUSAHAAN SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN KOMPETENSI WIRAUSAHA MAHASISWA PENDIDIKAN FISIKA UNIVESITAS INDRAPRASTA PGRI - Westri Andayanti (Jurnal Cakrawala Ilmiah, 2024)
Entrepreneurship education has become a crucial component in equipping students with relevant skills in the digital era. This study aims to analyze the implementation of entrepreneurship applications as a learning medium to enhance students' entrepreneurial competencies. The approach used in this research is quantitative, with a survey design conducted on 200 students participating in entrepreneurship education programs at several universities. The findings of the study indicate that the use of entrepreneurship applications significantly improves students' understanding of entrepreneurship concepts, managerial skills, and creativity in designing and running businesses. Additionally, the application facilitates the development of soft skills such as communication, decision-making, and risk management among students. Based on these findings, it can be concluded that entrepreneurship applications are effective as a learning medium that supports the development of students' entrepreneurial competencies. The recommendation from this research is the need for broader integration of application-based technology into entrepreneurship curricula in higher education to support a generation of innovative and adaptive entrepreneurs